Health Reform and the Uninsured: The New Requirements of the Old Ethics - Tunzi, Marc (The Hastings Center report, 2013)
U.S. health reform will raise many familiar ethical issues over the next several years-old issues in new forms. One of these is the fate of individuals who will still be uninsured after implementation of the Patient Protection and Affordable Care Act. One way to think about meeting their needs is to appeal to the 'social contract' around which the American Medical Association was originally formed. The AMA Code of Medical Ethics directs physicians to promote 'access to medical care for all people' and to 'share in providing care to the indigent.' I propose that a minimum standard of public service activities be defined and required by all U.S. medical specialties in order to maintain board certification and/or professional society membership.